Chimeric Antigen Receptors for T-Cell Malignancies - Scherer, Lauren D.; Brenner, Malcolm K.; Mamonkin, Maksim (Frontiers in Oncology, 2019)
Development of chimeric antigen receptor (CAR)-modified T cells for the treatment of T-lineage leukemia and lymphoma has encountered several unique challenges. The most widely expressed tumor antigen targets for malignant T cells are often also expressed on non-malignant T cells. Transducing T cells with CARs targeted to these shared antigens can therefore promote over-activation or fratricide of CAR T cells, reducing their therapeutic potency. If fratricide is resolved, clinical CAR T cell activity may eliminate normal T-cell subsets and cause temporary immunosuppression. In this review, we summarize the preclinical development of CAR-based therapies for T-cell malignancies and discuss strategies to minimize toxicities associated with on-target fratricide and off-tumor activity.